The impact of green technology innovation on global value chain upgrading in China’s equipment manufacturing industry - Li, Yan; Zhang, Xiaohan; Hao, Jinyun; Huang, Qingbo (Frontiers in Environmental Science, 2022)
In recent years, China’s equipment manufacturing industry has been actively embedded in the global value chain (GVC), but pollution emission has become an important factor hindering the industry from climbing to the high-end link of GVC. How to break through this restriction through green technology innovation is exactly urgent for the Chinese government and manufacturers. Therefore, using the panel data of China’s equipment manufacturing industry and its subsectors from 2007 to 2019, this paper constructs an econometric model to investigate the impact of green technology innovation on the GVC upgrading, and further examines the mediating effect through stepwise regression method. The results show that for the full samples of China’s equipment manufacturing industry, there is a U-shaped relationship between green technology innovation and the promotion of GVC status; and for basic metals and metal products manufacturing subsector and transport equipment manufacturing subsector, the conclusion is same with the whole industry; but for machinery equipment manufacturing subsector and electrical, electronic and optical equipment manufacturing subsector, the trend is opposite, that is, an inverted U-shaped relationship which first rises and then declines. Additionally, green technology innovation in China’s equipment manufacturing industry can promote GVC upgrading by reducing its dependence on GVC, optimizing export trade, reducing pollution costs, and promoting green product and process innovation. Based on the above, this paper finally proposes targeted policy implications to provide theoretical basis and experience reference for China’s equipment manufacturing industry to promote the GVC upgrading through green technology innovation.